Telling women's lives : the new biography - Wagner-Martin, Linda (New Brunswick, N.J. : Rutgers University Press, 1994)
Placing herself in the avid reader's chair, Linda Wagner-Martin writes about women's biography from George Eliot and Virginia Woolf to Eleanor Roosevelt and Margaret Mead, and even to Cher and Elizabeth Taylor. Along the way, she looks at dozens of other life stories, probing at the differences between biographies of men and women, prevailing stereotypes about women's lives and roles, questions about what is public and private, and the hazy margins between autobiography, biography, and other genres. In quick-paced and wide-ranging discussions, she looks at issues of authorial stance (who controls the narrative? who chooses which story to tell?), voice (is this story told in the traditional objective tone? and if it is, what effect does that telling have on our reading?), and the politics of publishing (why aren't more books about women's lives published? and when they are, what happens to their advertising budgets?).
Biography: the old and the new -- Telling women's lives -- The trap of the stereotype -- Relinquishing stereotypes -- The biographer's problem: women as wives -- A woman's self: wives and writers -- The power of naming -- Listening to women's stories -- Writing about mothers -- Taking control of story: women's voices -- Families of women -- The best of them -- Popular biography -- Revisionist biographies of women.
Includes bibliographical references (pages 183-192) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Englisch, ...; Umschulungswerkstätten für Siedler und Auswanderer; Biography as a literary form; Women -- Biography -- Methodology; Biography; Biographies as Topic; Biographie (Genre littéraire); Femmes -- Biographies -- Méthodologie.; Biographies; biographies (literary genre); biography (general genre); 17.86 literary genres, theory of genre; LANGUAGE ARTS & DISCIPLINES -- Rhetoric; REFERENCE -- Writing Skills; LANGUAGE ARTS & DISCIPLINES -- Composition & Creative Writing; Biography as a literary form; Women; Biografie; Frau; USA; Biografieën.; Vrouwen; Biographie (genre littéraire); Femmes écrivains anglaises -- Biographies -- Histoire et critique; Femmes écrivains américaines -- Biographies -- Histoire et critique; Geschichte 1880-1994.; Englisch; Biography as a literary form; Geschichte -- 1900-1993; Women -- Biography -- Methodology; Biography; Biographies; Biographies; Biographies